Creation of the staff motivation system of the culture organization at different stages of the career (Путеводитель предпринимателя, 2020)
At the present time organization culture is directed at solvingthe task ofincreasing productivity and quality of work, to ensure the best use of labor potential. To truly manage the worker motives of the organization of culture by means of influence on his personal interests, it is necessary to form a unified set of material, moral, artistic and other incentives.